Enterpreneurship Education in Darussalam Gontor Pesantren - Andi Triyawan; Qurrotu Aini Fa’izatun Sa’idah (Santri: Journal of Pesantren and Fiqh Sosial, 2022)
Pesantren is an ideal partner for government institutions to jointly improve the quality of education and the foundation of the nation's character. Pondok Pesantren Modern Darussalam Gontor is one of the largest educational institutions in Indonesia. All activities of students, teachers, and pesantren leaders always think about their interests in education so that the atmosphere of their lives also contains education. One of them applies entrepreneurship education to students in turn with the form of organization or administration. Entrepreneurship education is a debriefing to instill knowledge and skills and build personality traits that can create a generation that can be competitive, think creatively, behave innovatively, and be brave in facing the risks and challenges of life. The program organized to educate students in growing their entrepreneurial spirit is by managing the administration of cottages such as student cooperatives (kopel), canteen/cafeteria, health department, laundry department, photography department, mini market staff, Annisa Bakery, Annisa Noodle.